2017
DOI: 10.3892/mmr.2017.6478
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 regulates the differentiation of human adipose-derived stem cells to smooth muscle cells via targeting Krüppel-like factor 4

Abstract: Understanding the molecular mechanisms underlying human adipose-derived stem cell (hASC) differentiation to smooth muscle may contribute to the development of effective therapies for relevant muscle defects, such as bladder wall and urethral defects. A previous study described the differentiation of hASCs to smooth muscle cells (SMCs) by transforming growth factor-β1 (TGF-β1) and bone morphogenetic protein‑4 (BMP4) treatment. The present study investigated whether microRNA-145 (miR‑145) may be involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Frontiers in Cell and Developmental Biology frontiersin.org of the induction. They also demonstrated that the Krüppel-like factor 4 (KLF4) protein regulated the smooth muscle differentiation that was induced by BMP4 signaling (Aji et al, 2017). Furthermore, Lin et al (2020) revealed that N6-adenosine methyltransferases (Mettl3), an N6-methyltransferase that methylates adenosine residues at the N6 position of some RNAs, was upregulated following BMP4 induction.…”
Section: Mesodermal Differentiationmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org of the induction. They also demonstrated that the Krüppel-like factor 4 (KLF4) protein regulated the smooth muscle differentiation that was induced by BMP4 signaling (Aji et al, 2017). Furthermore, Lin et al (2020) revealed that N6-adenosine methyltransferases (Mettl3), an N6-methyltransferase that methylates adenosine residues at the N6 position of some RNAs, was upregulated following BMP4 induction.…”
Section: Mesodermal Differentiationmentioning
confidence: 99%